2016
DOI: 10.18267/j.aop.555
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Brand Equity and Perceived Value on Customer Revisit Intention: A Study in Quick-Service Restaurants in Vietnam

Abstract: The purpose of this study is to examine how brand equity, from a customer point of view, influences quick-service restaurant revisit intention. The authors propose a conceptual framework in which three dimensions of brand equity including brand associations combined with brand awareness, perceived quality, brand loyalty and perceived value are related to revisit intention. Data from 570 customers who had visited four quick-service restaurants in Ho Chi Minh City were used for the structural equation modelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 38 publications
1
22
1
6
Order By: Relevance
“…The perceived quality affects not only the customer's disposition to pay a higher price but is pivotal for a high cost-to-performance service strategy to work. Ultimately, perceived quality is the foundation of the customer's disposition to pay a higher price but not the only variable (Thi Minh Pham, Nga Do, & Minh Phung, 2016;Vera, 2015). When a customer thinks of a brand, the associations that come to the customer's mind can affect the pricing of the service and the customer's willingness to purchase.…”
Section: Perceived Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The perceived quality affects not only the customer's disposition to pay a higher price but is pivotal for a high cost-to-performance service strategy to work. Ultimately, perceived quality is the foundation of the customer's disposition to pay a higher price but not the only variable (Thi Minh Pham, Nga Do, & Minh Phung, 2016;Vera, 2015). When a customer thinks of a brand, the associations that come to the customer's mind can affect the pricing of the service and the customer's willingness to purchase.…”
Section: Perceived Qualitymentioning
confidence: 99%
“…A relationship marketer views the investment in the long-term customer interaction as an asset taking priority over the one-time exchange of a good or service. If a customer chooses to stay loyal with a brand long-term the brand has demonstrated customer retention assets, which is highly beneficial for brand health, especially in the service industry (Thi Minh Pham et al, 2016). McCrory, Pilcher, and McMillan 2017 Customer service begins with the culture of the company providing the service to the customer.…”
Section: Relationship Marketingmentioning
confidence: 99%
“…Tan et al (2015) indicated that the combination of brand aware-ness and perceived quality in fast food restaurant are crucial in the initial stage of brand building. Moreover, brand awareness and brand image also have a significant impact towards customer behavioral intention (Pham et al, 2016b). It is crucial to understand the effectiveness of relationship customer based brand equity to plan for the successful of street food such as food truck.…”
Section: Brand Equitymentioning
confidence: 99%
“…Furthermore, perceived quality also related to the customer's expectation towards a brand (Rodrigues & Martins, 2016). The customer personal perception in regards of experience with the product, unique needs and the situations and the insight of the customer will influence their decision making (Pham et al, 2016b). In the case of chain restaurant in Korea, the impact of perceived quality in the brand name leads the customer to patronage intention and word-of-mouth (Hyun & Kim, 2011).…”
Section: Perceived Qualitymentioning
confidence: 99%
See 1 more Smart Citation